Media and private advertising: Comments from international human rights standards - Aguirre, Federico; González, Juan Pablo (Universidad de Chile. Instituto de la Comunicación e Imagen, 2012)
Through international standards on human rights related with freedom of speech and human rights and companies, and in the context of the Chilean concentration on media property, the authors develop an analysis of the results of the study about media and private advertising in the case of the collusion of drugstores in the prices of medicaments.